PENGARUH MODEL PEMBELAJARAN KOMIDI PUTAR DISKUSI TERHADAP MINAT BELAJAR PPKn SISWA KELAS VII DI SMP NEGERI 2 BANGKO PUSAKO KABUPATEN ROKAN HILIR - Faima, Juli; Erlinda, Sri; Gimin, Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is based on the low interest of learning PPKn students in SMP Negeri 2Bangko Pusako Kabupaten Rokan Hilir. The formulation of the problem in this research is"Is there any significant effect ofKomidi Putar DiskusiWheel of Fortune learning model toward studentsâ€™ interest in learning PPKn at SMP Negeri 2 Bangko Pusako Kabupaten Rokan Hilir?â€. This study aims to determine the effect ofÂ  Wheel of Fortune learning model toward studentsâ€™ interest in learning PPKn at SMP Negeri2Bangko Pusako Kabupaten Rokan Hilir.This research was conducted at SMP Negeri2Bangko Pusako Kabupaten Rokan Hilir in April 2018. Â This research was a quantitative descriptive study that was experimental. Population in the study were students of class seven SMP Negeri 2 Bangko Pusako Kabupaten Rokan Hilir. The sample in this research was taken based on "Random Sampling" technique. Where the class taken into the sample was students of class VIII.1 (experimental class) given the learning model of Wheel of Fortune, and class VIII.4 (control class) were students who were given the conventional method. Then data analysis by using homogeneity test and "t" test. Based on the result of research indicated that there was an effect of learning interest between student who using Wheel of Komidi Putar Diskusi learning model and conventional method in SMP Negeri2 Negeri 2 Bangko Pusako Kabupaten Rokan Hilir.Where there was an average increase toward interest in learning PPKn of experimental classÂ  from26,43 Â Â to 28,06 and the average of PPKn learning interest of control class from25,96 Â Â to 26,13. Thus the hypothesis which reads that there is an effect of Komidi Putar Diskusiwheel of learning model toward studentsâ€™ interest in learning PPKn at SMP Negeri2Bangko Pusako Kabupaten Rokan Hilir, can be accepted.Â Key Words: Komidi Putar Diskusi, Interest to learning